The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.4093/dmj.2021.0166
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Interaction between Hyperuricemia and Abdominal Obesity as a Risk Factor for Metabolic Syndrome Components in Korean Population

Abstract: Background:The present study investigated the role of synergistic interaction between hyperuricemia and abdominal obesity as a risk factor for the components of metabolic syndrome. Methods: We performed a cross-sectional study using the data of 16,094 individuals from the seventh Korean National Health and Nutrition Examination Survey (2016 to 2018). The adjusted odds ratios of metabolic syndrome and its components were analyzed by multivariate logistic regression analysis. The presence of synergistic interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 48 publications
(51 reference statements)
2
8
0
Order By: Relevance
“…Mice body weights in the HF group were significantly higher than those in the other three groups, consistent with the established relationship between a high-fat diet and the accumulation of body weights. , However, our experiment showed that uric acid was not positively correlated with serum lipids. This finding is inconsistent with those of some previous studies, which suggested that hyperuricemia can lead to elevated lipid levels and ectopic fat deposition. ,, However, uric acid has excellent antioxidant properties at low concentrations and only functions as a pro-oxidant at high concentrations, which is harmful to the body .…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Mice body weights in the HF group were significantly higher than those in the other three groups, consistent with the established relationship between a high-fat diet and the accumulation of body weights. , However, our experiment showed that uric acid was not positively correlated with serum lipids. This finding is inconsistent with those of some previous studies, which suggested that hyperuricemia can lead to elevated lipid levels and ectopic fat deposition. ,, However, uric acid has excellent antioxidant properties at low concentrations and only functions as a pro-oxidant at high concentrations, which is harmful to the body .…”
Section: Discussionsupporting
confidence: 88%
“…27−29 Moreover, a high uric acid diet causes elevated blood lipids. 30,31 These results confirm that there is a mutual promotion between uric acid and blood lipids. 32 However, it is not clear whether high uric acid combined with high lipid levels has a reinforcing effect on PS.…”
Section: ■ Introductionsupporting
confidence: 64%
See 2 more Smart Citations
“…According to epidemiological surveys, the prevalence of HUA in Chinese adults remarkably rises from 8.4% in 2009–2010 to 14.0% in 2018–2019, and also more than 20.0% from 2007 to 2016 in United States ( 7 , 8 ). Although the serum UA level is not a diagnostic criterion for MetS, longitudinal studies have demonstrated that HUA is closely associated with the development of MetS and its components, and there is a bidirectional relationship between them ( 9 , 10 ). The morbidity of MetS gradually raises with the growth of serum UA level ( 11 ).…”
Section: Introductionmentioning
confidence: 99%